At what cost? A descriptive study evaluating cost awareness of laboratory investigations in doctors working in district hospitals in the West Coast and Cape Winelands districts - Brownbridge, Joshua (Stellenbosch : Stellenbosch University, 2019)
Thesis (MFamMed)--Stellenbosch University, 2019.